Leading transformation how to take charge of your company's future - Furr, Nathan R. (Harvard Business Review Press, 2018)
Leaders know that their job is to lead transformation to keep pace with technology and an ever-changing business environment. They also know that they are bound to fail doing so. But not because they can't solve a technology or strategy problem. They will fail because of the intractable human problems--fear, habits and routines, politics, the inability to see what doesn't yet exist--associated with change. These challenges are as old as the hills, but what if there were finally a way to transcend them? This book reveals a radical new method for doing just that. Written by the manager who designed and implemented it, the neuroscientist who helped make it work, and the academic who explains why it works and how to do it, Leading Transformation introduces an innovative yet proven process for creating breakthrough change. Broken down into three steps-envisioning the possible, breaking down resistance, and prototyping the future-this process uses cutting edge tools such as science fiction, artifact trails and neuroprototypes to overcome people's inability to conjure up or react to what doesn't yet exist, override powerful habits and routines that prevent people from changing, and create compelling non-linear narratives about the organization's future and how to get there. Used successfully by organizations such as Lowe's, IKEA, Levi's, Microsoft, Google and NASA--with numerous other companies around the world learning how to apply it-the process revealed in this book gives leaders the means to effectively transcend the human barriers that hold organizations back.-- Provided by publisher.